Effect of Butler’s Sciatic Nerve Mobilisatision in Low Back Pain Patients with Sciatica - Dr. Bindu Sarfare (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Lumbar-spine disorders rank fifth among disease categories and the health care. Intervention in patients with a disease requires that the intervention has to be more beneficial, safer, and cost-effective. This dilemma is particularly important in patients with low back dysfunction (LBD) with radiculopathy.[1] Methodology 30 patients as diagnosed cases of low back pain radiating to posterior or lateral aspect of the lower limb with positive Straight Leg Raise Test (SLRT). Subjects were randomly allocated to the Experimental and the Control group. Both the groups (n=30) were treated with conventional physiotherapy treatment and Butler’s sciatic nerve mobilisation, given to the experimental group only. All the subjects were assessed at pre-treatment & post-treatment sessions using ROM of hip with SLRT, numerical rating scale (NRS) and Rolland Morris questionnaire. Data analysis Pre & post data was analysed using paired T test. Result Rolland Morris scores at the end of the treatment session showed an 85.46% improvement and t value of hip ROM showed 3.207, hence neural mobilisation was found to be more effective in the treatment of sciatica.